Analysis of Yield of Eleutherosides B and E in Acanthopanax divaricatus and A. koreanum Grown with Varying Cultivation Methods - Jeong Min Lee; Myoung-Hee Lee; Suk-Bok Pae; Ki-Won Oh; Chan-Sik Jung; In-Youl Baek; Sanghyun Lee (The Scientific World Journal)
An analysis of the yield of eleutherosides B and E in Acanthopanax divaricatus and A. koreanum was performed using high performance liquid chromatography to evaluate production by different cultivation methods. In A. divaricatus and A. koreanum, the total content of eleutherosides B and E was 2.466–7.360 mg/g varying by plant section, 3.886–11.506 mg/g by pinching site, 3.655–10.083 mg/g by planting time, and 3.652–10.108 mg/g by fertilizer ratio. Thus the total content of eleutherosides B and E in A. divaricatus and A. koreanum differed depending on cultivation methods. These results present useful information for high eleutheroside content applications in A. divaricatus and A. koreanum. This information can affect selection of plant section and cultivation methods for nutraceutical, pharmaceutical, and cosmeceutical material development.